The image in French philosophy - Trifonova, Temenuga (Consciousness, literature & the arts, 2007)
The Image in French Philosophy challenges dominant interpretations of Bergson, Sartre, Lyotard, Baudrillard and Deleuze by arguing that their philosophy was not a critique but a revival of metaphysics as a thinking pertaining to impersonal forces and distinguished by an aversion to subjectivity and an aversion of the philosophical gaze away from the discourse of vision, and thus away from the image. Insofar as the image was part of the discourse of subjectivity/representation, getting rid of the subject involved smuggling the concept of the image out of the discourse of subjectivity/representa.